Propriété, cadastre et usages locaux dans les campagnes françaises (1789-1960) Histoire d'une tension légale - Gaveau, Fabien (Les Cahiers de la MSHE Ledoux, 2021)
The French Revolution undertook to rationalize the right of ownership by including it in land ownership. However, the country's situation forces us to tolerate uses that form the basis of the relationship with the land. The definition of a new tax system, with the tax registry as a reference, encourages the valuation of the owner of the land, which the censal suffrage benefits until 1848. However, from Corsica to the North, from Brittany to Alsace, from the Pyrenees to the Ardennes, living environments present specificities that are difficult to satisfy the desires of promoters of private land rights. Until the 1960s, this conflictual relationship was the matrix for the definition of farming.